LINGUISTIC EVALUATION OF PUPIL'S KNOWLEDGE - KRISOVA, Zdenka (Journal of Technology and Information Education, 2012)
The evaluation is a natural part of any educational activity. It is often expressed quantitatively evaluation stage (usually a sign of 1-5, or AF point), but increasingly also applied qualitative assessment - verbal (language), which provides comprehensive information about student and better able to capture their individual progress. Evaluation of student knowledge level should always be objective, should motivate the creative student activities, increase his interest in teaching, strengthen its activity. Properly assess each pupil in the teaching process is extremely demanding and responsible, so teachers are always looking for ways to improve their work. One possibility is the use of information technology as a means of supporting the right decision about the quality of teacher knowledge of the pupil. Expert systems as programs that simulate the decision-making activity of experts to solve highly complex, highly focused problem-solving, can be a solution to this problem to good use. As part of this post was created fuzzy logic expert system for assessing the level of knowledge of the language learner and computer simulation was performed language model of the evaluation process.
Keywords: evaluation; expert systems; expert knowledge; fuzzy set; linguistic fuzzy rule; fuzzy model; fuzzy logic; approximate reasoning